Risk perception of climate change: Empirical evidence for Germany - Manuel Frondel; Michael Simora; Stephan Sommer (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
The perception of risks associated with climate change appears to be a key factor for the support of climate policy measures. Using a generalized ordered logit approach and drawing on a unique data set originating from two surveys conducted in 2012 and 2014, each among more than 6,000 German households, we analyze the determinants of individual risk perception associated with three kinds of natural hazards: heat waves, storms, and floods. Our focus is on the role of objective risk measures and experience with these natural hazards, whose frequency is likely to be affected by climate change. In line with the received literature, the results suggest that personal experience with adverse events and personal damage therefrom are strong drivers of individual risk perception. – – Die Wahrnehmung von Risiken, die mit dem Klimawandel einhergehen, wird als wesentlicher Faktor für die Unterstützung von Klimaschutzmaßnahmen in der Bevölkerung erachtet. Auf Basis eines Generalized-Ordered-Logit Ansatzes und eines Datensatzes, der auf zwei Erhebungen aus den Jahren 2013 und 2015 unter jeweils mehr als 6000 Haushalten beruht, werden in diesem Papier die Determinanten der individuellen Risikowahrnehmung von drei Naturereignissen analysiert: Hitzewellen, Stürme und Überschwemmungen. Im Fokus der Analyse befinden sich die Rolle von objektiven Risikomaßen und die persönliche Erfahrung mit solchen Ereignissen. In Übereinstimmung mit der empirischen Literatur deuten unsere Ergebnisse darauf hin, dass persönliche Erfahrung mit diesen Ereignissen und dadurch erlittene Schäden die individuelle Risikoeinschätzung stark beeinflusst.
Keywords: D81; H31; Q54; 330; Damage experience; natural hazards; generalized ordered logit